تأديب قضاة المحكمة الجنائية الدولية - مفيد نايف تركي الراشد (PROSPECTIVE RESEARCHES, 2023)
There is a very important principles which rules the Judges’ job and gives this job a certain specified position. This position is the Independence of Judiciary which makes the judiciary an independent authority from legislative and executive authorities and that can ensure the rule of law and extend the role of Judges to cover all legal disputes without any intervention of other authorities. This principle is one of the most important elements of the just judiciary. In terms of the subject of discipline، A system of discipline judges should be adopted in a way that does not harm the principle of judges’ independency. This system should not be as a tool of punishing or threating judges. As, the system of discipline judges may use to achieve personal issues or political goals. For all what is provided، the scientific desire motivated me to search in this topic through explain the concept of a judge، what is the violations which the judges may do when they practice their job? What are the discipline procedures which may be taken against them? How they can appeal the penalties? Finally, how we can ensure the Independence of Judges’ job in the range of discipline them.